2006
DOI: 10.2134/agronj2005.0348
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Manure Compost Improves Soil and Increases Tall Wheatgrass Yield

Abstract: There is a need to identify alternative uses for composted manure applications. The objectives in this study were to 1) document the effect of composted dairy manure on soil agronomic characteristics, and 2) evaluate tall wheatgrass yield response to six rates of composted dairy manure. A field trial with a split-plot randomized complete block design and four replications was initiated on a Windthorst sandy loam soil (Udic Paleustalfs) in north-central Texas near Stephenville in September of 2001. Main plots w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 26 publications
6
47
0
Order By: Relevance
“…Frequently, the best rate is the highest, as supported by Butler and Muir (2006), who observed the greatest tall wheatgrass dry matter yield with the highest composted dairy manure rate of about 180 t ha −1 . More specifically, forage yield increased from 32 to 96% with 11.2 and 179.2 t compost ha −1 , respectively, in the first of two growing seasons.…”
Section: Yield Responsementioning
confidence: 81%
See 2 more Smart Citations
“…Frequently, the best rate is the highest, as supported by Butler and Muir (2006), who observed the greatest tall wheatgrass dry matter yield with the highest composted dairy manure rate of about 180 t ha −1 . More specifically, forage yield increased from 32 to 96% with 11.2 and 179.2 t compost ha −1 , respectively, in the first of two growing seasons.…”
Section: Yield Responsementioning
confidence: 81%
“…Butler and Muir (2006) observed that soil pH increased on average by 0.5 units as the dairy manure compost rate doubled in magnitude from 11.2 to 179.2 t ha −1 . As previously explained, with long-term compost use the residual effects on crop production and soil properties can last for several years, since only a fraction of the N and other nutrients becomes available for plants in the first year after spreading (Hartl et al, 2003;Eghball et al, 2004).…”
Section: Chemical Fertilitymentioning
confidence: 98%
See 1 more Smart Citation
“…Many other authors reported no effect on pH (Bevacqua and Mellano, 1994;Crecchio et al, 2001;Zebarth et al, 1999). However, there are several studies that revealed either an increase of acidic soil (Hue, 1992;Whalen et al, 2000;Baziramakenga et al, 2001;Butler and Muir, 2006;Valarini et al, 2009) or a decrease (Chang et al, 1991), While increasing pH is clearly valuable in terms of improving microelement availability, lowering pH should be limited to avoid enhancing the solubility of toxic elements. In this study, we did not detect Cd, Ni or Pb and most other heavy metals such as Cr, Zn, Mn, Ba, Sr and Ti were detected at very low concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Manure improves physicochemical properties of soils thereby enhancing water infiltration and root penetration [35,36] and thus promoting plant tillering. On the other hand, manure amendment in acidic soils increases soil pH, mineral N, available P, K and Ca [18,37].…”
Section: Wheat Growthmentioning
confidence: 99%